2016
DOI: 10.7860/jcdr/2016/19345.8776
|View full text |Cite
|
Sign up to set email alerts
|

Current Development of Anti-Cancer Drug S-1

Abstract: S-1 is a novel oral fluoropyrimidine derivative, widely used for treating gastric, pancreatic, lung, head, neck and breast carcinomas. It is designed to enhance the clinical utility of an oral fluoropyrimidine and is associated with low gastrointestinal toxicity. S-1 consists of three pharmacological agents (at a molar ratio of 1:0.4:1)-Tegafur (FT), a prodrug of 5-Fluorouracil (5-FU), 5-Chloro-2-4-Dihydroxypyridine (CDHP), which inhibits the activity of Dihydropyrimidine Dehydrogenase (DPD) and Oxonic Acid (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…This was a single-center, single-arm, nonrandomized trial. Another limitation of our study was that we did not test the levels of thymidylate synthase (TS), orotate phosphoribosyl-transferase (OPRT) and dihydropyrimidine dehydrogenase (DPD), which were considered potentially being associated with the efficacy and safety of S-1 [ 22 ]. Due to potential difference between Westerners and Asians in pharmacokinetics and pharmacodynamics of S-1, it is recommended that the plasma concentration, and effectiveness and toxicity related biomarkers (TS and DPD) should be monitored and examined if the similar regimen is applied to Western patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a single-center, single-arm, nonrandomized trial. Another limitation of our study was that we did not test the levels of thymidylate synthase (TS), orotate phosphoribosyl-transferase (OPRT) and dihydropyrimidine dehydrogenase (DPD), which were considered potentially being associated with the efficacy and safety of S-1 [ 22 ]. Due to potential difference between Westerners and Asians in pharmacokinetics and pharmacodynamics of S-1, it is recommended that the plasma concentration, and effectiveness and toxicity related biomarkers (TS and DPD) should be monitored and examined if the similar regimen is applied to Western patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAP is approved for the treatment of colon cancer, metastatic colorectal cancer, and metastatic breast cancer (Pratt, McLeod, Dean, Malheiro, & Rubinstein, ). S‐1 is composed of tegafur combined with 2 modulators of 5‐FU activity, gimeracil, and potassium oxonate (oteracil) and is used for treating gastric, pancreatic, lung, head, neck, and breast carcinomas (Chhetri et al, ; Ter Veer et al, ). The frequency of HFS induced by CAP is 51–78% (Degen et al, ; Miller, Gorcey, & McLellan, ).…”
Section: Introductionmentioning
confidence: 99%
“…CDHP inhibits 5‐fluorourcil degradation in liver, which results in the maintenance of the 5‐fluorourcil concentration in the body. S‐1 is used for therapies for various cancers, such as breast, gastric, and pancreatic cancers . The previous study has reported that S‐1 administration inhibits metastasis of a high lung‐metastatic subline of a basal‐like breast cancer cell line, MDA‐MB‐231, in a mouse xenograft model .…”
Section: Introductionmentioning
confidence: 99%